Procena faktora koji utiču na percepciju teledentističkih usluga pacijenata - Risanti, Ika Oktaviani; Dewanto, Iwan (Scripta Medica, 2022)
Background/Aim: The trend of using teledentistry increased significantly during the pandemic. Many studies have analysed patients' perceptions of teledentistry, but no studies have examined the factors that influence these perceptions. Aim of this study was to determine the factors that influence the patient's perception of teledentistry.Methods: This type of research was a descriptive analysis with a cross sectional design. A total of 170 respondents filled out a questionnaire containing sociodemographic data and statements with a Likert scale related to the five perceptual domains of teledentistry. The data were analysed for correlation test with SPSS and model test with SEM-PLS.Results: There were only two factors, namely age and level of education that appear as factors that affect the patient's perception with a correlation significance value of 0.001 for age and 0.005 for education. The value of the correlation coefficient was positive, which means that the higher the age and level of education, the tendency of the perceived value to be more strongly agreed. These results were reinforced by the results of the coefficient values ​​on the SEM-PLS model test which were positive and significant, namely 0.311. The results of the goodness of fit analysis in this study were in the moderate category with a value of 0.265. However, the imbalance in the number of respondents in each sociodemographic group makes the results of this study less representative. Conclusion: There was a significant positive correlation between the level of education and the perception of teledentistry. This means that the higher a person's education level, the better his perception of teledentistry. Age had a significant correlation and influence with the patient's perception of teledentistry. A positive value on a significant test result indicated that the higher the age, the better the patient's perception of teledentistry.